Ensaio clínico controlado e randomizado para avaliação da eficácia da azitromicina no tratamento da bronquiolite aguda - Luisi, Fernanda (2012)
Rationale: Acute viral bronchiolitis is a leading cause of hospitalization in the first year of life. Several studies have shown that macrolides have immune modulating properties, but only a few and underpowered trials have tested the efficacy of these antibiotics in infants with acute bronchiolitis. In this study we tested the hypothesis that azithromycin reduces the length of hospitalization and oxygen requirement in infants with acute bronchiolitis. Methods: We performed a randomized, double-blind, placebo-controlled trial. Infants aged less than 12 months were admitted to one university hospital with a clinical diagnosis of acute bronchiolitis (first wheezing episode). They were randomized to receive either oral azithromycin (10 mg/kg/day) or placebo administered once daily for seven days. Clinical data were recorded and nasopharyngeal samples for viral identification were collected at enrollment. Main outcomes were length of oxygen requirement and duration of hospitalization. Results: The study included 105 infants with a mean age of 3.4 months (sd ± 2.6) (50 in the intervention, and 55 in the placebo groups) from 2009 to 2011. Patients were comparable with respect to baseline clinical characteristics and viral identification. There were neither differences between the two groups regarding duration of hospitalization (5.42 ± 2.96 [azithromycin] vs 6.54 ± 3.56 [placebo] days; p=0.200), nor for oxygen requirement. 62/101 (61.38%) patients had positive viral immunofluorescence and 57 (56.4%) were due to respiratory syncytial virus (RSV). Conclusions: This is the first trial to test the efficacy of macrolides on acute viral bronchiolitis in a large sample of hospitalized infants. Routine treatment with azithromycin does not improve length of hospitalization in infants with the first episode of wheezing. This finding may potentially reduce antibiotic overuse that carries along the risk for increasing overall antibiotic resistance. Still, one cannot rule out possible beneficial effects of different classes of macrolides, or even a positive association to specific wheeze phenotypes/genotypes.